Evaluasi Implementasi dan Kendala Manajemen Resiko Pendidikan dalam Penanggulangan Narkoba di Kalangan Remaja Kabupaten Jepara - Siti Aqidatun; Sisca Septiani (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to analyze the evaluation of implementation and the constraints of educational risk management in combating drug abuse among adolescents in Jepara Regency. This research employs a qualitative approach, utilizing observation, interviews, and documentation as data collection methods. The escalation in the number of cases leading up to 2025—which places Jepara as the second-highest in Central Java—reflects a failure in governance to detect social risks at an early stage. This has broad implications across three primary aspects: operational risk, manifested as declining academic achievement and disrupted learning effectiveness; reputational risk, which erodes public trust in educational institutions; and accreditation risk, resulting from the schools' inability to meet social quality assurance indicators. The high prevalence of drug abuse among adolescents in Jepara is not merely a common issue of juvenile delinquency, but rather a systemic threat that requires intervention through integrated risk management functions. There is an urgent need for educational institutions to adopt a systematic risk management framework to ensure the sustainability of quality and a secure learning environment. By integrating risk management as a core function of governance, schools can transform from a responsive-curative approach to a proactive-preventive paradigm. This strategic step is key to maintaining compliance with accreditation regulations, protecting institutional integrity, and, most importantly, ensuring the safety and future of the younger generation as a national asset against the destructive threat of narcotics